Kajian Literatur: Aspek yang Mempengaruhi Regulasi Emosi Guru Sekolah Dasar - Muh. Saldin; Fadhilah Ahmad Qaniah; Widi Candika Pakaya (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2024)
Teachers' emotional regulation is a crucial aspect in the success of the learning process in elementary schools. Teachers' ability to manage emotions not only affects personal well-being, but also the quality of interactions with students and the effectiveness of learning. This study aims to identify and analyze various aspects that influence the emotions of elementary school teachers through a systematic literature review. This literature review uses a systematic review approach by analyzing 20 articles from Google Scholar published between 2005-2023. Articles were selected based on the following criteria: (1) focus on teacher emotional regulation, (2) research subjects of elementary/primary school teachers, (3) publication in reputable journals, and (4) clear research methodology. The analysis shows that elementary school teachers' emotional regulation is influenced by five main categories: (1) Personal factors (age, experience, self-efficacy), (2) Student factors (student behavior, academic achievement), (3) Work environment factors (coworker support, school climate, workload), (4) Organizational factors (school policies, climate reform), and (5) Work-life balance factors (personal-professional life balance). Primary school teachers’ emotion regulation is multifactorial and complex. A comprehensive understanding of these factors is essential for developing effective intervention programs to improve teacher well-being and learning quality.